2014
DOI: 10.1371/journal.pone.0086980
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Musical Training on Understanding Voiced and Whispered Speech in Noise

Abstract: This study tested the hypothesis that the previously reported advantage of musicians over non-musicians in understanding speech in noise arises from more efficient or robust coding of periodic voiced speech, particularly in fluctuating backgrounds. Speech intelligibility was measured in listeners with extensive musical training, and in those with very little musical training or experience, using normal (voiced) or whispered (unvoiced) grammatically correct nonsense sentences in noise that was spectrally shaped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
135
6
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(162 citation statements)
references
References 38 publications
17
135
6
4
Order By: Relevance
“…However, the complex, binaural nature of the scenes presented in our task (particularly the dual backgrounds) failed to reveal any musician advantage. Moreover, a recent investigation of musician versus non-musician performance on measures of voiced and unvoiced speech perception in noise (Ruggles et al, 2014) failed to show any musician advantage -a finding partly in agreement with our non-linguistic results.…”
Section: Auditory Scene Analysissupporting
confidence: 92%
See 2 more Smart Citations
“…However, the complex, binaural nature of the scenes presented in our task (particularly the dual backgrounds) failed to reveal any musician advantage. Moreover, a recent investigation of musician versus non-musician performance on measures of voiced and unvoiced speech perception in noise (Ruggles et al, 2014) failed to show any musician advantage -a finding partly in agreement with our non-linguistic results.…”
Section: Auditory Scene Analysissupporting
confidence: 92%
“…Musicians' long experience in musically-based scene analysis may also be a causal factor in their enhanced ability to comprehend speech when the speech signal is masked by noise (classic 'energetic' masking) or multi-talker babble (energetic plus so-called 'informational masking' -see footnote 4; Parbery-Clark et al, 2009a, 2009b, 2011Strait & Kraus, 2011b;Strait et al, 2012b; but see also Patel, 2011). However, recent data suggest that musicians and non-musicians do not differ in susceptibility to informational and energetic masking during speech-in-noise perception (Ruggles et al, 2014).…”
Section: Auditory Scene Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, evidence for such a transfer has been mixed, and when observed, the effect has been minimal: studies measuring speech perception in steady or multi-talker babble noise showed either no, or only small, musician advantage (Parbery-Clark et al, 2009;Fuller et al, 2014b;Ruggles et al, 2014). Perception of speech in such background noises is not a situation recognized as relying on fine F0 processing.…”
Section: Introductionmentioning
confidence: 99%
“…Studies comparing nonmusicians with musicians who began training early in life have revealed a "signature" set of enhancements associated with musical experience (27,28). Relative to nonmusician peers, musicians tend to show enhanced speech-innoise perception (29)(30)(31)(32)(33)(34), verbal memory (30)(31)(32)(33)(35)(36)(37)(38), phonological skills (39)(40)(41)(42)(43)(44)(45), and reading (46-50), although not without exception (51,52). Music training has also been linked to enhancements in the encoding of sound throughout the auditory system.…”
mentioning
confidence: 99%